Navigating Pain: A Clinical inquiry into Marma Chikitsa for Kashtartava (Primary Dysmenorrhea) Alleviation - Varsha, Varsha; Arya, Tarun; Sharma, Priyanka; Verma, Ananya; Pal, Ashok (Journal of Neonatal Surgery, 2025)
Introduction: Pain is a natural and universal human experience, an acute reminder of our frailty and the complexity of our life. Unpleasant sensory experiences like pain are distinct from others like touch, warmth, and cold. Through a variety of peripheral nerves, a harmful signal from the periphery is sent to the spinal cord. Kashtartava i.e., dysmenorrhea is not separately described as a disease anywhere in Ayurvedic classics. But there are many other diseases in which Kashtartava is considered and described as a symptom. The purpose of this study is to gather scientific evidence on the effectiveness, safety, and feasibility of Marma Stimulation. By understanding this healthcare providers will be able to provide a range of evidence-based options for managing primary dysmenorrhea, allowing for personalized and holistic care that goes beyond pharmaceutical solutions. Methodology: 101 diagnosed cases of primary dysmenorrhea with regular menstrual cycle were selected from OPD of Parul Ayurved Hospital between the age group of 18- 25 years. They were administered Marma Chikitsa once daily during premenstrual phase for two consecutive cycles. Pain, the duration of analgesia, and the use of pain medication were assessed before and after the intervention. Observations and Results: A significant decrease in pain (p<0.005) was observed after the intervention of Marma Chikitsa, with a more long-lasting analgesia and improvement in working ability, duration as well as intensity of pain (p<0.005) and decreased need for pain medication. Conclusion: In females with primary dysmenorrhea Marma Chikitsa was able to promote nearly complete analgesia, and the analgesia persisted for at least one additional menstrual cycle even after the treatment was stopped. Patients also got relief in the pre-menstrual symptoms like nausea, vomiting, lethargy and tenesmus. Use of analgesic drugs were significantly reduced post treatment.